REPRESENTASI FEMINISME DAN KRITIK SOSIAL ATAS PERAN PEREMPUAN DALAM “YUNI 2021” (STUDI ANALISIS SEMIOTIKA MODEL ROLLAND BARTHES) - Sekar Pawestri (UNIVERSITAS STEKOM, 2025)
This study focuses on the analysis of the representation of feminism and social critique of women's roles depicted in the film